2016
DOI: 10.1016/j.compbiomed.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale CFD simulations of the transitional and turbulent regime for the large human airways during rapid inhalation

Abstract: The dynamics of unsteady flow in the human large airways during a rapid inhalation were investigated using highly detailed large-scale computational fluid dynamics on a subject-specific geometry. The simulations were performed to resolve all the spatial and temporal scales of the flow, thanks to the use of massive computational resources. A highly parallel finite element code was used, running on two supercomputers, solving the transient incompressible Navier-Stokes equations on unstructured meshes. Given that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 33 publications
1
67
0
Order By: Relevance
“…Analysis of the motion of the jaw, tongue, pharyngeal walls, soft palate, and epiglottis revealed how each region of anatomy influences the volume of the airspace and the cross‐sectional area of the upper airway along its length. Many studies have previously shown the relationship between airway cross‐sectional area and airway resistance, with narrower sections increasing the subject's work of breathing. Therefore, mapping the dynamic behavior of the upper airway cross‐section throughout a breath is vital to accurately predicting the airway pressure losses in computational and experimental models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the motion of the jaw, tongue, pharyngeal walls, soft palate, and epiglottis revealed how each region of anatomy influences the volume of the airspace and the cross‐sectional area of the upper airway along its length. Many studies have previously shown the relationship between airway cross‐sectional area and airway resistance, with narrower sections increasing the subject's work of breathing. Therefore, mapping the dynamic behavior of the upper airway cross‐section throughout a breath is vital to accurately predicting the airway pressure losses in computational and experimental models.…”
Section: Discussionmentioning
confidence: 99%
“…The air was considered incompressible and isothermal at 37°C. In addition to solving the equations for the conservation of mass and momentum, large eddy simulation (LES) was employed to model sub‐grid scale turbulence as previous studies have shown this technique to be effective at modeling the turbulent and transitional flow regimes within the airway . The procedure to solve the Navier‐Stokes equations in a moving mesh was implemented as previously described .…”
Section: Methodsmentioning
confidence: 99%
“…By imposing the same inflow for each nostril, the differences between the left/right cross-sections H. Calmet et al Journal of Aerosol Science 115 (2018) 12-28 explains these elevated velocities. These higher local flow rates are due to the small cross-sectional area of the nasal valve leading to a jet like flow (Calmet et al, 2016;Doorly, Taylor, Gambaruto, Schroter, & Tolley, 2008). These narrow undulated and intricate passageways produce drastically H. Calmet et al Journal of Aerosol Science 115 (2018) 12-28 different flow fields.…”
Section: Airflow Field Resultsmentioning
confidence: 99%
“…They found that the complex flows were produced from the transient flow over a wide range of Reynolds numbers. From their study, it was found that the turbulent level is higher in the throat than in the nose [89].…”
Section: Applicationsmentioning
confidence: 97%
“…In order to carry out the simulation, 110,000 time-steps were required on 480 cores that required~20 hours, and 20,000-30,000 mesh elements were used on each core to maintain a good parallel efficiency [88]. Calmet et al (2016) conducted the large-scale CFD stimulation of the transitional and turbulent flow by using two supercomputers to solve the transient Navier-Strokes equation [89]. The lung geometry in the study composed of an exterior face and the airways from the nasal cavity to the third lung bifurcation.…”
Section: Applicationsmentioning
confidence: 99%